Analysis of the Hospital Information System (SIRS) on the Performance of the Medical Record Unit at RSUD - Andi Kusmawan; Reny Aprinawaty; Novita Br Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: RSUD Sultan Sulaiman in Serdang Bedagai Regency faces challenges in implementing the Hospital Information System (SIRS), particularly in the medical record unit. Although several departments have started implementing SIRS, manual record-keeping is still practiced in the medical record unit, leading to delays in patient data flow and a lack of coordination between units. Research Objectives: This study aims to analyze the implementation of SIRS at RSUD Sultan Sulaiman, focusing on the medical record unit, and to identify the factors that hinder the system's implementation. This research also provides recommendations to improve the efficiency of medical data management. Research Methodology: This research uses a qualitative approach with descriptive analysis methods. Data was collected through interviews with pharmacy officers, head of the pharmacy department, head of the medical record unit, and direct field observations. Thematic analysis was used to identify the factors hindering and benefiting the implementation of SIRS. Research Results: The implementation of SIRS has expedited administrative processes and improved coordination between units. However, challenges related to human resources, training, and inadequate hardware continue to hinder optimal implementation. Conclusion: Intensive efforts in training, provision of adequate hardware, and regular system evaluation are needed to support the optimal implementation of SIRS, which is expected to improve the efficiency of medical services at RSUD Sultan Sulaiman.